Enhancing learning interest and physical fitness through game-based physical activities among elementary school students - Ilmul Ma'arif; Risfandi Setyawan; Rendra Wahyu Pradana (Bima Loka: Journal of Physical Education, 2026)
This study examined the effect of game-based physical activities on elementary school students’ learning interest and physical fitness. A quantitative approach with a one-group pretest-posttest design was employed. The participants were 55 fourth-grade students from Pandanwangi State Elementary School, selected through purposive sampling. The intervention consisted of game-based physical activities implemented over eight weeks during Physical Education (PE) classes. Physical fitness was assessed using a standardized field-based fitness test consisting of a 40-m sprint, bent-arm hang, sit-ups, standing long jump, and 600-m run. Learning interest was measured using a questionnaire covering four dimensions: attention to learning materials, interest in learning activities, perseverance in participation, and active engagement during the learning process. Data were analyzed using descriptive statistics and paired-samples t-tests. The findings revealed significant improvements in both physical fitness and learning interest following the intervention (p < 0.001). The mean physical fitness score increased from 13.85 to 16.11, representing a 16.27% improvement, while the mean learning interest score increased from 52.60 to 72.84, representing a 38.47% improvement. Furthermore, the proportion of students achieving the high physical fitness category increased from 7.2% to 29.1%, whereas those demonstrating high learning interest increased from 18.18% to 54.5%. These findings indicate that game-based physical activities effectively enhance both the physical and affective outcomes of elementary school students. In conclusion, integrating game-based physical activities into Physical Education instruction provides an engaging learning environment that promotes students’ physical fitness and learning interest. Therefore, this approach is recommended as an effective instructional strategy for elementary school Physical Education.